Spatial analysis of the phenomenon of poverty in Nasiriyah using geographic information systems technology - jwad, Ass.Lec Hassen Talib (Thi Qar Arts Journal, 2023)
The research aims to diagnose the factors of poverty in the city of Nasiriyah, and its spatial analysis by adopting spatial analyzes in the environment of the geographic information systems program by finding patterns of spatial distribution of the poor population and the factors and density of their distribution such as (neighborhood, nucleus density, kernel coefficient, and hot spots) with identifying the factors causing this phenomenon, As well as studying their conditions and the resulting effects. (665) questionnaires were distributed to a few houses in the city of Nasiriyah with varying distribution. The intentional sample was used to select a number of poor people according to their distribution in the residential neighborhoods. Measurements were also adopted to treat them statistically according to the characteristics, size and quality of the data obtained. The research reached a set of indicators represented by the clear contrast of the phenomenon of poverty in the urban sphere of the city of Nasiriyah and its housing units, as the population and housing factors interact with each other to formulate the most important factors influencing the phenomenon of poverty through the close interdependence between them, as most of the neighborhoods of the city of Nasiriyah suffer from urban problems, and among them suffer from Poverty to varying degrees.